PIK3R3 promotes chemotherapeutic sensitivity of colorectal cancer through PIK3R3/NF-kB/TP pathway. Issue 3 (4th March 2018) - Ibrahim, Sidikjan; Li, Guodong; Hu, Fuqing; Hou, Zhenlin; Chen, Qianzhi; Li, Geng; Luo, Xuelai; Hu, Junbo; Feng, Yongdong
ABSTRACT: Phosphoinositide-3-kinase regulatory subunit 3(PIK3R3) is overexpressed in different types of human cancer. We previously reported the important role of PIK3R3 in colorectal cancer (CRC). However, the prognosis effect of PIK3R3 in CRC is still remaining unclear. In this study, we explored online clinical databases to analyze the prognosis differences between higher and lower expression of PIK3R3 in CRC patients. Interestingly, we found that better disease-free survival (DFS) were occurred in patients with higher expression of PIK3R3, but there is no significant difference in overall survival (OS). For further, we showed that PIK3R3 could enhance 5-FU induced apoptosis by regulating the expression of thymmidine phosphorylase (TP). In conclusion, PIK3R3 could be considered as a predictor of 5-FU sensitivity for personalized treatment, and a therapeutic target for colorectal cancer.